Assessment of Emotional Intelligence in Facilitators of Government and Private Sector Medical College - Syeda Mahnoor, Akhtar Ali, Ayesha Zulfiqar, Syed Shehryar, Alisha Zulfiqar, Santosh Kumar (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluates the EQ level in facilitators of government and private medical colleges of Karachi. Study design: Cross sectional Place and duration: Ziauddin Medical College, January-June 2022 Methodology:Facilitators of government and private sector medical institutes particularly lecturers were targeted population. The calculated sample; (n=35/institute) was recruited by simple random technique. The questionnaire regarding demographic data was self-developed however, emotional quotient was assessed by EQ scale. Chi-square test was applied as test of significance. Results: The maturity scale score of females showed that statistically (p-value=0.011) they are emotionally more mature than males. When sensitivity and maturity score were compared between the two institutes (Government or private) their scores were similar and there was no significant difference between sensitivity and maturity scores of government and private sector employees. According to EQ compatibility scoring system scale ,100% male and 100% female scored in the range of extremely high competency category. Conclusion: The emotional quotient analysis showed that females are more sensitive and mature emotionally than males though the emotional intelligence of male and female participants was equal. Emotional sensitivity, maturity and intelligence scores of Government and private sector employees was comparable to each other. Keywords: Emotional quotient, Medical education system, Facilitators, Government and private sector